Using Facebook as a Blended Learning tool in professional training (Mayéutica Revista Científica de Humanidades y Artes, 2020)
We present the experience of the use of Blended Learning or BLearning, as it is known massively, as a functional pedagogical support strategy in the training of university professionals, specifically the Nursing Program of the Universidad Centroccidental Lisandro Alvarado. Facebook, one of the most demanded social networks was specifically used to create a closed group in which information related to the programming of activities, support material, photographs and case studies was made available to students, multimedia files for reinforcement of information, assessment instructions and assignment of reading material for reporting. The use of this methodology is recent, but due to the results obtained be of habitual implementation.
Keywords: B Learning; pedagogical strategy; experience; support; vocational training